Систематичне положення роду Rhus L. - Kovalchuk, T.D. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2011)
Native and foreign literary sources are analyzed in order to study nomenclature and systematics of Rhus L. genus.